HUBUNGAN PENGETAHUAN, DUKUNGAN KELUARGA DAN DUKUNGAN PETUGAS KESEHATAN DENGAN KEPATUHAN IBU HAMIL MENGKONSUMSI TABLET FE DI PUSKESMAS LUBUK BATANG - Yeyen Warizqin Karima; Suprida Suprida; Arie Anggraini; Mastina Mastina (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Compliance with consuming Fe tablets is said if pregnant women consume all of the Fe tablets given during pregnancy. Adherence of pregnant women consuming Fe tablets is an important factor in ensuring an increase in hemoglobin levels of pregnant women. This type of research was an analytic observational study with a cross-sectional approach or design. sectional. The population in this study amounted to 103 people and the sample in this study were pregnant women at 36 weeks' gestation totaling 30 respondents. The results of bivariate research on the relationship between knowledge, family support and health worker support with adherence of pregnant women to consuming Fe tablets based on the chi square statistical test of knowledge p-value 0.007 <0.05 OR 13.500, family support p-value 0.024 <0.05 OR 11,000 and support Health workers p-value 0.007 < 0.05 OR 0.074 It can be concluded that there is a relationship between knowledge, family support and health worker support simultaneously with the compliance of pregnant women consuming Fe tablets in the working area of the UPTD Puskesmas Lubuk Batang, Ogan Komering Ulu Regency in 2023. Suggestions to respondents It is hoped that in this study pregnant women will get important information about pregnancy, especially regarding the need for Fe tablets during pregnancy and pregnant women are expected to consume Fe tablets together with vitamin C so that the absorption of Fe tablets can be optimal.